2013
DOI: 10.1159/000346751
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Characteristics, Biochemical Recurrence and Functional Outcome in Radical Prostatectomy Patients on Statin Therapy

Abstract: Introduction: We assessed the pathological characteristics of the radical prostatectomy specimen, the rate of biochemical failure and the functional outcome after surgery, in terms of incontinence and erectile dysfunction rate, in patients on statin medication. Materials and Methods: A total of 588 patients with a mean age 65.2 years (SD = 5.7 years) participated in the study. All patients were contacted and interviewed. Results: Users who had been on statin medication for more than 2 years had lower levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…A total of 3229 publications were identified during the initial search (see Additional file 1. ), and after employing exclusion criteria, a total of 22 studies were included for PCa recurrence analysis 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 ( Table 1 ), 8 trials were available for PCa-specific mortality 22 30 31 32 33 34 35 36 ( Table 2 ), and 13 for BCR-free survival analysis 8 9 11 14 17 20 25 29 36 37 38 39 40 ( Table 3 ). Among 22 studies included in meta-analysis for PCa recurrence, 14 included a population primarily treated with radical prostatectomy (RP).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 3229 publications were identified during the initial search (see Additional file 1. ), and after employing exclusion criteria, a total of 22 studies were included for PCa recurrence analysis 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 ( Table 1 ), 8 trials were available for PCa-specific mortality 22 30 31 32 33 34 35 36 ( Table 2 ), and 13 for BCR-free survival analysis 8 9 11 14 17 20 25 29 36 37 38 39 40 ( Table 3 ). Among 22 studies included in meta-analysis for PCa recurrence, 14 included a population primarily treated with radical prostatectomy (RP).…”
Section: Resultsmentioning
confidence: 99%
“…Patients in this trial were followed 588 patients (mean age of 65.2 years) for a median of 3.4 years [34].…”
Section: Radical Prostatectomymentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16] A recent meta-analysis showed that statins reduce the total incidence of PCa as well as the risk of clinically important advanced PCa. 17 Although several individual studies have indicated a beneficial effect of statins in reducing BCR risk and cancer-specific mortality after diagnosis, [18][19][20] meta-analyses have not revealed a consistently significant effect. 21 Meta-analyses have also failed to show a significant association between metformin use and PCa incidence.…”
Section: Introductionmentioning
confidence: 99%